2011
DOI: 10.3844/ajisp.2011.17.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunomodulatory Effect: Selection of the Correct Targets for Immunostimulation Study

Abstract: Problem statement: Numerous plants or remedies that are traditionally used for various diseases had been claimed to maintain general good health, particularly the immune system. With the advanced understanding on immunology and ethnopharmacology, study on the interaction of this herb with the immune system is critical to understand the safety and its efficacy as a potent immunomodulatory agent. Approach: Selecting proper immune cells from a suitable immune organ allowed for the understanding on the mode of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…PHA, a lectin isolated from red kidney bean ( Phaseolus vulgaris ), primarily stimulates T cell proliferation and it has a slight effect on B cells. This lectin stimulate blastogenesis of T lymphocytes by interaction with CD2 to stimulate the production of IL-2 and IFN-γ [10]. For this study it was observed through repeated stimulation of PBMCs that proliferative effect of PHA normally peaks after 48 h of stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PHA, a lectin isolated from red kidney bean ( Phaseolus vulgaris ), primarily stimulates T cell proliferation and it has a slight effect on B cells. This lectin stimulate blastogenesis of T lymphocytes by interaction with CD2 to stimulate the production of IL-2 and IFN-γ [10]. For this study it was observed through repeated stimulation of PBMCs that proliferative effect of PHA normally peaks after 48 h of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…This may provide a possible explanation for the observed pro- and anti-inflammatory effects of by uMakhonya® doses under different physiological stimuli. The potential uses of immunomodulators in clinical medicine include treatment of immunodeficiency caused by AIDS and suppression of immune response in autoimmune disease [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant mitogens such as lectins are glycoproteins that nonspecifically bind to cell surfaces and stimulate cells to undergo mitosis [37]. However, these are selective in triggering T or B cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…PHA has been shown to stimulate T cell proliferation and minimal activity on B cells. The resulting activation of T lymphocytes via interaction with CD2 stimulates the production of IL-2 and IFN- γ [21]. As observed in previous studies using similar models, the proliferative effect of PHA normally peaks after 48 hours of stimulation [22].…”
Section: Discussionmentioning
confidence: 89%